Effectiveness of Pyrethroid-Piperonyl Butoxide Nets Versus Standard Pyrethroid-Only Nets in Preventing Malaria in Children Under 10 Years Living in Kisantu Health Zone, Democratic Republic of the Congo - Gillon Ilombe; Joris Losimba Likwela; Philippe Lukanu; Aimée Lulebo; Nicole Muela; Joachim Mariën; Kennedy Makola Mbanzulu; Baby Mabanzila; Junior Rika Matangila; Fiacre Agossa; Eric Mukomena; Sylvie Linsuke; et al. (Tropical Medicine and Infectious Disease)
Democratic Republic of the Congo (DRC) is among the countries that have a high malaria incidence. In an effort to combat this public health challenge, innovative tools and strategies are being developed and evaluated. Among the new generation of nets with improved effectiveness of insecticides, those treated with a combination of piperonyl butoxide (PBO) and pyrethroids appear to be a promising malaria control tool. This study evaluated the effectiveness of this combination under community conditions of use in the DRC. A quasi-experimental study was carried out from January to December 2018, in Kisantu Health Zone. Thirty villages were randomly allocated as clusters (1:1) to receive one of two types of long-lasting insecticidal nets (LLIN) treated with deltamethrin alone, or PBO with deltamethrin. After the intervention, the assessments were conducted monthly, quarterly, and every six months for malaria infection, mosquito density, and LLIN durability, respectively. Comparison of changes in different indices between the two groups was made using generalized linear models to correct for non-linear effects. A total of 1790 children were included. There was a significant non-linear effect of time (months) on the malaria infection incidence. The malaria infection incidence was higher in January–March, May–June, and November. It remained higher in the control group compared to the intervention group over time. Similarly, there was a significant non-linear effect of time on the density of both Anopheles funestus s.l. and Anopheles gambiae s.l. These densities decreased after the first month following the intervention and increased after 6 months. Twelve months later, a cohort follow-up showed that the bio-efficacy of LLINs was better in the intervention group. The nets treated with the combination of PBO and deltamethrin appear to be more effective for malaria control under community conditions in the DRC, but a loss of chemical durability is noted after the first year of use.